Association Of Horizontal Strabismus And Refractive Errors For Children In Baghdad, Iraq - Noori, Ahmed Rassol; Taher, Akeel Hadi (Medical Science Journal for Advance Research, 2024)
Background: This research project intended to inquire affiliation betwixt comitant esotropia & exotropia & refractive error among children in Baghdad city, Iraq. The term strabismus is derived from the Greek word strabismos and means ocular misalignment. This deviation may be caused by abnormalities in binocular vision or by abnormalities in the neuromuscular control of eye movements. An esodeviation is manifest convergent misalignment of the visual axes. An exodeviation is a manifest (exotropia) or divergent strabismus. Ametropias can also be classified according to the nature of the mismatch between the optical power and eye length. In myopia, the eye has too much optical power relative to its axial length, and (with accommodation relaxed) light rays from an object at infinity converge too soon and thus focus in front of the retina. This results in an out of focus image on the retina; the far point of the eye is located at the front of the eye, between the cornea and optical infinity point. In hyperopia, the eye does not have enough optical power for its axial length, and (with accommodation relaxed) an object at infinity will focus behind the retina, again producing an out of focus image on the retina; the far point of the eye (actually a virtual point, not a real point in space) is behind the retina. Method: In this cross-sectional study, 200 strabismic patients participated. After written informed consent was obtained, the children underwent a complete ophthalmic examination, with uncorrected and corrected visual acuity as well as cycloplegic refraction. Strabismus is defined as; an inward deviation and an outward deviation of 10 or more prism diopters. Results: This study included 200 patients ,114 (57%) female and 86 (43%) male .According to the strabismus 150 (75%) with esotropia case and 50 (25%) with exotropia. Of the 200 patients 173 (86.5%) were hyperopic and remaining 27 (13.5%) were myopic. Conclusion: This study found a close association between refractive error and horizontal strabismus in children in Baghdad city, Iraq. These findings may help establish guidelines for early correction of refractive errors to prevent the development of strabismus and amblyopia.